EFEKTIVITAS PEER COUNSELING UNTUK MENINGKATKAN KEMANDIRIAN SISWA DALAM MENGAMBIL KEPUTUSAN KARIR PADA SISWA KELAS XII SMK NURUL ISLAM JAKARTA TIMUR - Sabar Sabar; Laras Puspito Arum (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2016)
The background of this research important of the students have autonomy in makingcareer decisions. Independence in decision-making is very important to have a studentcapable of handling its own problems and is responsible for the decisions taken.The purpose of this research to determine whether the peer counseling effective forincreasing students' independence in making decisions vocational students Nurul Islam XIIclass AK 1 in the academic year 2015-2016.This research is a quantitative Quasi Experiment. Calculations for researchquestionnaire test or reliability test use Alpha Croanbach with reliability coefficient of0.903144 (acceptable) with strong reliability levels and questionnaires using Likert scale usedto measure attitudes, opinions and perceptions of a person or group of events or socialphenomena. Reported the 51 items that can be used for research of 60 questions that exist.The population in this study were all students of class XII SMK Nurul Islam 2015-2016 school year as many as 153 students. Sempel taken that class XII with a sample of 15students AK1 control group and experimental group of 15 students. The technique ofcollecting data using questionnaires independence in making career decisions. Datavalidation using the product moment applied to ms. Excel. Analysis of data using teknikt-testwith Ms.Excel and manual calculations.Based on this research, using t-test is Thitung 6.21> Ttabel 0.048 which means, theresults alternative hypothesis, Peer Counseling effective in improving students' independencein making career decisions of students of class XII AK 1 SMK Nurul IslamBibliography: 1 Al-Qur’an, 13 books (1990-2014), 3journal (1993-2013), 4 thesis (2013-2015), 5 article (2010-2014), 1 paper (2013)